2020
DOI: 10.1002/cam4.3263
|View full text |Cite
|
Sign up to set email alerts
|

Exosome–transmitted microRNA‐133b inhibited bladder cancer proliferation by upregulating dual‐specificity protein phosphatase 1

Abstract: Bladder Cancer (BC) is the ninth most common tumor in the world and one of the most common malignant tumors of the urinary system. Some studies reported that miR‐133b expression is reduced in BC, but whether it plays a role in the development of BC and its mechanism is unclear. microRNAs can be packaged into exosomes to mediate communication between tumor cells, affecting their proliferation and apoptosis. The objective of this study was to investigate the effect of exosomal miR‐133b on BC proliferation and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…In addition, we found that exosomal miR-133b might be involved in inhibiting BC proliferation by rearranging the dual-specific protein phosphatase 1 (DUSP1). These findings could hold new hope for BC treatment directions [ 166 ]. In conclusion, their results provide strong evidence that exosomal miR-133b acts as a tumor inhibitory agent targeting DUSP1 in BC proliferation.…”
Section: Applications Of Nanomaterials In Treatment Of Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that exosomal miR-133b might be involved in inhibiting BC proliferation by rearranging the dual-specific protein phosphatase 1 (DUSP1). These findings could hold new hope for BC treatment directions [ 166 ]. In conclusion, their results provide strong evidence that exosomal miR-133b acts as a tumor inhibitory agent targeting DUSP1 in BC proliferation.…”
Section: Applications Of Nanomaterials In Treatment Of Bcmentioning
confidence: 99%
“…In addition, exogenous miR-133b can be ingested by BC cells, reducing the malignant phenotype of BC cells. Exosomal miR -133b or other miRNAs better distinguished the disease and make specific advances in the treatment of BC [ 166 ].…”
Section: Applications Of Nanomaterials In Treatment Of Bcmentioning
confidence: 99%
“…Currently, available data regarding exosome utilization in BC treatment are limited. Cai et al examined the effect of exosomal miR-133b on BC cell proliferation both in vitro and in vivo [ 71 ]. The authors isolated exosomes from BC tissue and serum from BC patients, as well as exosomes from BC cell lines (T24 and 5637), reversely transcribed RNA into cDNA and subsequently performed RT-PCR using miR133b specific primer.…”
Section: Evs As Potential Therapeutic Vectorsmentioning
confidence: 99%
“…Studies have shown that the expression level of miR-133b in BCa tissues is significantly reduced, which was significantly correlated with LNM ( 94 ). MiR-133b may inhibit the proliferation of BCa by up-regulating dual-specificity protein phosphatase 1 (DUSP1) ( 11 ). It inhibited angiogenesis and enhanced BCa cells’ chemosensitivity to Gemcitabine by targeting transgelin 2 (TAGLN2) ( 14 ).…”
Section: Regulation Of Micrornas For Bca Patients With Lymph Node Metmentioning
confidence: 99%